Analisis Penerapan Program Mitigasi Bencana Pada Badan Penanggulangan Bencana Daerah - Pandu Sakti; Faizal Anwar; Rekho Adriadi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
ABSTRACT The purpose of this research is the implementation of policies of the Bengkulu Province disaster management agency in disaster mitigation. This research method uses descriptive qualitative research. The results of the study explained that the implementation of policies of the Bengkulu Province Regional Disaster Management Agency (BPBD) for the implementation of disaster mitigation policies had been running quite well. The Regional Disaster Management Agency of Bengkulu Province in Disaster Mitigation has issued a policy on natural disaster reduction, namely the Disaster Resilient Village policy and the proportion of Disaster safe schools. Apart from implementing this policy, the Bengkulu Province Disaster Management Agency also carries out socialization activities for disaster preparedness. In implementing this policy, we also cooperate with other agencies to carry out activities or policies in making Bengkulu Province safe from disasters. The conclusions of this study indicate that the policies issued by the Bengkulu Province BPBD in Mitigation are regulated in Governor Regulation Number 34 of 2018 concerning increased preparedness. Among them are disaster-disaster village policies and disaster-safe Madrasah schools. Keywords: Disaster, Mitigation, Policy.